Thin Film-Based Solar Cell and Dye-Sensitized Solar Cells: Review - Ho Soon Min*, Hardani, Cari , Agus Supriyanto (International Journal of Advanced Science and Technology, 2020)
The need for energy in the world continues to increase from year to year. At this time, the need for energy is obtained from sources of energy that are conventional, and non-renewable, such as coal, and gas and petroleum. Deposits from these energy sources will be reduced, whereas energy needs are increasing. To address these problems, alternative energy sources can help to reduce dependence on renewable energy sources. The dye-sensitized solar cell was discovered by Michael Gratzel in 1991. Many researchers have developed this type of solar cell by trying different types of natural dye from plant extracts. The dye is commonly used and achieves the highest efficiency is the type of ruthenium complex. Solar energy is expected to grow rapidly from time to time due to the rising demand for commercial and residential applications. Metal chalcogenide thin films have been prepared by using various deposition method including physical deposition method and chemical deposition technique. The obtained sulfur, selenium, tellurium based thin films could be employed as absorber materials in solar cell application. The photovoltaic parameters were studied and the power conversion efficiency could be reached up to 21%.